2021
DOI: 10.1210/clinem/dgab651
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Somatotroph Adenoma-derived Exosomes: Characterization of Nonhormonal Actions

Abstract: Context Identification and biological actions of pituitary-derived exosomes remain elusive. Objective To validate production of exosomes derived from human and rat pituitary and elucidate their actions. Methods Isolated extracellular vesicles (EVs) were analyzed by Nanoparticle Tracking Analysis (NTA) and expressed exosomal markers detected by Western blot, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In our study, we assessed the alterations in serum miRNA levels during radiotherapy. It has been reported that the levels of miRNAs in cells and those derived from serum exosomes are essentially concordant [ 45 ]. The upregulation of serum miR-143-3p and miR-223-3p levels during radiotherapy could serve as an early indicator of radiosensitivity in ESCC, displaying an AUC ≥ 0.7 in predicting both OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we assessed the alterations in serum miRNA levels during radiotherapy. It has been reported that the levels of miRNAs in cells and those derived from serum exosomes are essentially concordant [ 45 ]. The upregulation of serum miR-143-3p and miR-223-3p levels during radiotherapy could serve as an early indicator of radiosensitivity in ESCC, displaying an AUC ≥ 0.7 in predicting both OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that there are only a few studies about the role of EVs in the hypothalamus and most of them concern POMC neurons [213][214][215]. There are, however, several studies regarding pituitary EVs, mainly in an attempt to determine biomarkers of pituitary adenomas [416][417][418]. In a recent study, hydrocortisone stimulated the release of EVs from pituitary somatotroph cells [417].…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several studies regarding pituitary EVs, mainly in an attempt to determine biomarkers of pituitary adenomas [416][417][418]. In a recent study, hydrocortisone stimulated the release of EVs from pituitary somatotroph cells [417].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zhou et al reported that exosomes of GHPA cell line treated colon cancer cell line (HCT116 cell line) showed decreased malignancy in vitro and decreased tumor metastasis in HCT116 xenografted nude mice (11). This decreased malignancy occurs proposed through altered gene expression in the p53 and MAPK pathways (11). In addition, Zhao et al indicates that low miR-423-5p levels promote tumorigenesis in somatotropic adenomas (53).…”
Section: Ghpasmentioning
confidence: 99%
“…The secretory quantity and content of exosomes can vary according to their biogenesis, cell of origin, and physiological or pathological cell status. Among these, noncoding RNAs (ncRNAs) are enriched and stable in exosomes and are important owing to their regulatory function in tumor initiation and progression, including in PA (10,11).…”
Section: Introductionmentioning
confidence: 99%